PENJUALAN PRODUK UMKM SECARA ONLINE PADA SITUS PESONA JNE DI TENGAH PANDEMI MSME’S ONLINE SELLING THROUGH PESONA JNE WEBSITE IN PANDEMIC - Darmeinis (Pusat Riset dan Inovasi Nasional, 2023)
Abstrac : One of the most important pillars in Indonesia economy is MSMEs (Micro Small Medium Enterprises). But unfortunately, currently the pandemic become the one of the biggest problems for MSMEs to survive. COVID-19 pandemic changed all human lives, especially in the economic aspect. This crises cause income decreased and even so many company terminated their employee. Not only that, there are so many government regulations which cause restrictions to be able to increase their sales transactions of MSMEs products. Unbalanced between production and operation causing loss at their end. Offcourse, in this case, creativity and innovation are needed to be able to survive. Currently, MSMEs must do business development, innovate and keep fighting in the midst of modernization. The utilization of digital platform as the one of media promotion and MSMEs sales channel turned out to be less influential, due to the decrease in consumer purchasing power. Cooperation and support from various parties are needed, especially from government, marketplace and logistic companies that care about MSMEs which affected by the pandemic.